Acceptance, safety, and impact on quality of life of exergame for elderly patients with neurodegenerative diseases: A systematic review and meta-analysis - Tsurayya, Ghina; Duta, Teuku F.; Naufal, Muhammad A.; Alina, Meulu; Isitua, Chinwe C.; Ohanu, Ernest C. (Narra X, 2023)
The aim of this study was to evaluate the efficacy, safety, adherence, and acceptance of exergame in improving the quality of life (QoL) among elderly patients with neurodegenerative diseases. A systematic search was conducted in PubMed, Embase and Scopus for relevant studies up to 16 March 2023. Quality of the included studies were assessed using Cochrane’s Risk of Bias tool version 2.0. Meta-analysis using a random effect was conducted on outcomes reported at least by two studies to calculate the standard mean difference (SMD) and its 95% confidence interval (CI). The difference of influence between exergame and conventional therapy was judged based on Z- and p-values. Heterogeneity was determined by I2 score. As many as 15 studies were included (n=466 participants) published between 2013–2023. Nine studies had ‘high quality’ five studies had ‘some concerns’, and one had ‘high risk’. Results from meta-analyses suggests that the exergame does significantly not improve the QoL among patients with Parkinson’s diseases. Similarly, no statistically significant difference (p>0.05) of QoL improvement among Alzheimer’s disease patients receiving exergame intervention. No adverse effects were reported to be associated with the intervention, and in fact, the patients experienced reduced fatigue and fear of falling. Patients in intervention group showed high acceptance and adherence to the therapy, which could be attributed to exergame being enjoyable, easy-to-use, and motivational. In conclusion, despite exergame being highly acceptable and relatively safe, the intervention does not improve the QoL of the elderly patients.